2003
DOI: 10.1046/j.1432-1033.2003.03584.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides from hylid and ranin frogs originated from a 150‐million‐year‐old ancestral precursor with a conserved signal peptide but a hypermutable antimicrobial domain

Abstract: The dermal glands of frogs produce antimicrobial peptides that protect the skin against noxious microorganisms and assist in wound repair. The sequences of these peptides are very dissimilar, both within and between species, so that the 5000 living anuran frogs may produce ≈ 100 000 different antimicrobial peptides. The antimicrobial peptides of South American hylid frogs are derived from precursors, the preprodermaseptins, whose signal peptides and intervening sequences are remarkably conserved, but their C‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
200
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(218 citation statements)
references
References 75 publications
8
200
0
10
Order By: Relevance
“…Studies of preserved museum specimens have found the earliest B. dendrobatidis infection in X. laevis from South Africa in 1938, and enzootic infections were found in nondeclining populations in South Africa (Weldon et al, 2004). Antimicrobial peptide defenses may evolve more readily than components of the adaptive immune system (Zasloff, 2002;Vanhoye et al, 2003). Rapid peptide variation may result from error-prone DNA polymerases (Vanhoye et al, 2003).…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of preserved museum specimens have found the earliest B. dendrobatidis infection in X. laevis from South Africa in 1938, and enzootic infections were found in nondeclining populations in South Africa (Weldon et al, 2004). Antimicrobial peptide defenses may evolve more readily than components of the adaptive immune system (Zasloff, 2002;Vanhoye et al, 2003). Rapid peptide variation may result from error-prone DNA polymerases (Vanhoye et al, 2003).…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 99%
“…Antimicrobial peptide defenses may evolve more readily than components of the adaptive immune system (Zasloff, 2002;Vanhoye et al, 2003). Rapid peptide variation may result from error-prone DNA polymerases (Vanhoye et al, 2003). As disease advances through Panama, there is the opportunity to study this strong selection pressure on the evolution of peptide immune defenses.…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 99%
See 1 more Smart Citation
“…These highly-efficient host-defence compounds that are secreted from the skins of amphibians are attracting ever-increasing scientific attention, as it seems that they may be good templates for the development of new antibiotics designed to combat the emergence of pathogens that are resistant to conventional antibiotics. As many studies have shown, amphibian skin secretions not only produce potent broad-spectrum antimicrobial peptides, but also a number of peptides that have very similar structures and biological activities to mammalian neuropeptides and hormones, such as the bombesins, bradykinins and tachykinins [1][2]. In early research, hundreds or even thousands of amphibians were sacrificed to obtain enough material for biological and chemical analyses, though as modern methods and technologies have developed, this killing has become unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…3 These secretions not only produce large amounts of biologically active peptides that are similar to mammalian neuropeptides and hormones, but they also contain a rich arsenal of broad-spectrum, cytolytic antimicrobial peptides. 4,5 Their high degree of chemical complexity is evidenced by the fact that they contain proteins, peptides, biogenic amines, alkaloids and other as yet uncharacterized biochemicals. Interestingly, peptides have o5 kDa molecular mass are the predominant molecules in the secretions of many frogs, 6 Five thousand living anuran frog species may produce about 100 000 different antimicrobial peptides.…”
Section: Introductionmentioning
confidence: 99%